Forty years of the Journal of Futures Markets: A bibliometric overview - Baker, H. Kent; Kumar, Satish; Pandey, Nitesh (The journal of futures markets, 2021)
This study uses bibliometrics to present a retrospective on the Journal of Futures Markets (JFM) on its 40th anniversary. The Journal's annual number of publications and citations grew substantially, with US‐affiliated authors being the dominant contributors. Authorship analysis reveals an increase in collaboration and diversity among JFM authors. Bibliographic coupling analysis reveals that the Journal's main themes include commodities, volatility, trading, hedging, arbitrage and pricing, forecasting volatility, and credit default swaps. Its primary citation drivers are article age, article length, number of authors, FT100 affiliation, and references.